Mastering Microsoft Dynamics CRM 2016 : an advanced guide for effective Dynamics CRM customization and development - Somani, Deepesh (Packt Publishing, 2017)
This comprehensive guide covers all the essential features of Dynamics CRM so you can build effective applications About This Book Harness the full power of Dynamics CRM 2016 through real-world scenarios Create efficient client-side applications and customized plugins that work seamlessly across mobile and the Web Get to know the best practices from field experience to utilize Dynamics CRM 2016 efficiently Get an in-depth understanding of mobility and tablet options for Dynamics CRM 2016 Who This Book Is For This book is for those with Dynamics CRM knowledge who want to utilize the latest features available with Dynamics CRM 2016 and Update 1. Extensive Dynamics CRM development experience would be beneficial. What You Will Learn Learn to manage the sales, service, and marketing divisions of any organization using entities and other Dynamics CRM 2016 customizations Learn about the XRM framework of Dynamics CRM 2016 and leverage its features Provide an enhanced mobile and tablet experience using the latest features of Dynamics CRM Get an enhanced Dynamics CRM analytics experience with Word and Excel templates Develop client-side applications using JavaScript and Web API How to develop plugins and workflows using Dynamics CRM 2016 Solution framework improvements, new field types, and Relevant Search in Dynamics CRM 2016 In Detail Microsoft Dynamics CRM is the most trusted name in enterprise-level customer relationship management. The latest version of Dynamics CRM 2016 comes with some exciting extra features guaranteed to make your life easier with Dynamics CRM. This book provides a comprehensive coverage of Dynamics CRM 2016 and helps you make your tasks much simpler while elevating you to the level of an expert. The book starts with a brief overview of the functional features and then introduces the latest features of Dynamics CRM 2016. You will learn to create Word and Excel templates, using CRM data that will enable you to provide customized data analysis for your organization. You will understand how to utilize Dynamics CRM as an XRM Framework, gain a deep understanding about client-side scripting in Dynamics CRM, and learn creating client-side applications using JavaScript and Web API. We then introduce visual control frameworks for Dynamics CRM 2016 mobile and tablet applications. Business Process Flows, Business Rules, and their enhancements are introduced. By the end of this book, you will have mastered utilizing Dynamics CRM 2016 featur ...